Shared epitope 'homozygosity' is strongly associated with rheumatoid arthritis in Turkey - (:unkn) unknown (OXFORD UNIV PRESS, 1998)
Objective. Associations with HLA-DRB alleles, implicated in the aetiopathogenesis of rheumatoid arthritis (RA), are found to be different in various ethnic groups. This study aimed to investigate DRB1 alleles in RA patients in Turkey. Methods. The DRB region of the MI-IC was screened by polymerase chain reactian/sequence-specific oligonucleotide (PCR/SSO) hybridizations in 101 seropositive Rh patients and compared with 101 healthy controls. Results. Significant differences were in the frequencies of DRB1*0404 (12 vs 1, P = 0.003, OR = 13.5), *0401 (19 vs 4, P = 0.001, OR = 5.6) and *0408 (5 vs 0, P = 0.06, OR = 11.6) between RA patients and controls. The shared epitope (SE) was present in 70.2% of RA patients compared to 31.6% of controls (P < 0.0001, OR = 5.1). A double dose of SE was considerably more frequent in the RA group (21 vs 1, P < 0.0001, OR = 26.5). Conclusion. These results support the reported positive association of RA with SE in seropositive patients in Turkey, and emphasize 'SE homozygosity' as the most strongly associated genetic susceptibility marker for RA.
Keywords: rheumatoid arthritis; HLA association; shared epitope; HLA-DR; SUSCEPTIBILITY; DISEASE; SEVERITY; HYPOTHESIS; HLA-DR4